Le collège-lycée Gérôme à Vesoul (1610-2019) : retour sur une démarche originale de préservation de collections patrimoniales - Liliane Hamelin; Romain Joulia (In Situ)
As the closure of the former lycée Gérôme in Vesoul (a former middle school that later became a high school) in June 2019 drew near, the department of Haute-Saône, concerned with preserving a unique heritage, developed an original approach aimed at bringing together the skills of specialised institutions and contributors. On the basis of a detailed inventory drawn up for this purpose, a scientific committee met to assess the interest of the different collections and to determine the most suitable destination in connection with heritage institutions in the region.Although these objects have suffered from their storage conditions in one of the school's attics since 1975 (date on which they changed its status to “collège”, an equivalent of middle school or comprehensive school), 500 items have been inventoried and photographed. They concern the fine arts (plaster casts intended for drawing lessons), the teaching of natural sciences (educational posters, human and animal skeletons), physics and literature.Ordered from catalogues of specialised producers, some of the artefacts of the lycée Gérôme are present in other inventoried collections like those of the lycée Gambetta of Tourcoing or the lycée Guez-de-Balzac of Angoulême.Two private collections of liturgical garments and objects have just been added to these items’ inventories, related to the presence of a chaplaincy and the mineralogical collection of Paul Petitclerc (1840-1937), native of Vesoul, a reputed ornithologist and president of the French geological society.